Label‐free detection of polysulfides and glycogen of Cyanidium caldarium using ultra‐multiplex coherent anti‐Stokes Raman scattering microspectroscopy. (13th May 2021) - Oka, Yuki; Yoshida, Masaki; Minoda, Ayumi; Leproux, Philippe; Watanabe, Makoto M.; Kano, Hideaki
Abstract: Living microalga Cyanidium caldarium was visualized using ultra‐multiplex coherent anti‐Stokes Raman scattering (CARS) microspectroscopy. The Raman band related to the SO4 2− ion at 982 cm −1 was detected at the peripheral part of the cells and showed a signal amplitude that was approximately threefold larger than that in the medium, indicating accumulation of SO4 2− ions. Depending on the incubation conditions, a broad and sharp Raman band at approximately 505 cm −1 was observed at the peripheral part and inside the cells, respectively. Based on comparison of the results with model substances, these broad and sharp bands were assigned to polysulfides and glycogen, respectively. Abstract : Ultra‐multiplex coherent anti‐Stokes Raman scattering microspectroscopy was applied to the living microalga Cyanidium caldarium . Depending on the incubation conditions, intracellular polysulfides (upper, red) were visualized, which showed a spectroscopic signature around 505 cm −1 with a broad bandwidth of 60 cm −1 (red). Intracellular glycogen (lower, green) was also visualized as a sharp Raman band around 505 cm −1 with a sharp bandwidth of 19 cm −1 (green). Based on our spectroscopic analysis, polysulfides and glycogen were spectrally separated to obtain each CARS image.